How does climate exacerbate root causes of conflict in Nigeria? Climate Security Pathway Analysis - Dutta Gupta, Tanaya; Madurga Lopez, Ignacio M.; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Nigeria, using an impact pathway analysis. Three main impact pathways are identified: 1) Resource availability and access pathway; 2) Livelihood and food insecurity pathway; 3) Fossil fuels, environmental impacts, and livelihood insecurity pathway.